x+-3=-11

Simple and best practice solution for x+-3=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+-3=-11 equation:



x+-3=-11
We move all terms to the left:
x+-3-(-11)=0
We add all the numbers together, and all the variables
x+8=0
We move all terms containing x to the left, all other terms to the right
x=-8

See similar equations:

| 24x+3=22 | | c=16−–2 | | 4b+2=10b= | | -3(x+15)+4–5x=2+10x-7.x=-3x=-2Gx=32x=7​ | | 4x-6-2x=2x+3+3x | | 18=x/4=7 | | 4x=23-0.5(4x+16 | | 4x=23-0.5(4x+16) | | 4(3z=2)=9z-7 | | 20=y/3+12 | | 50+20x=35 | | /8k-6=6(k+3)+6k | | 10y-1=3y+2 | | x+57=3x | | y=3X+205 | | -5+3x=100 | | 6x2-5x-29=0 | | a+3,178=6,000* | | 0.4x-18=1.1x-25 | | (4x-9)=(X+14 | | 18=3n=6n | | .5/20=p/100 | | 6+3(6x-7)=18x+15 | | g-10=-13 | | -8v+4.74=2.34-8.4v | | -2(x+1)=-2x+5-7 | | 45=x+82 | | 18=7x-5x | | 8x+11=71 | | 6(g-2)=15 | | f-12=-76 | | 9f=3f |

Equations solver categories